A thiophene-modified doubleshell hollow g-C3N4 nanosphere boosts NADH regeneration via synergistic enhancement of charge excitation and separation. Issue 8 (26th March 2019) - Meng, Jialin; Tian, Yao; Li, Congfa; Lin, Xue; Wang, Zhenyang; Sun, Liming; Zhou, Yinuo; Li, Jiansheng; Yang, Nan; Zong, Yongchao; Li, Feng; Cao, Yingxiu; et al.
Abstract : ATCN-DSCN enabled boosted NADH photo-regeneration and FDH-assisted CO2 reduction. Abstract : Low efficiency in photo-regeneration of redox-active cofactors is a crucial bottleneck in restricting artificial bio-photosynthesis of fuel systems from practical applications. We herein developed novel thiophene-modified doubleshell hollow g-C3 N4 nanospheres (ATCN-DSCN) via synergistically enhancing both the charge excitation and separation processes to efficiently photo-regenerate nicotinamide adenine dinucleotide (NADH), which was then utilized as the cofactor by formate dehydrogenase (FDH) to reduce CO2 to form formic acid. The ATCN-DSCN material exhibited outstanding optical and photoelectrical properties, enabling a NADH yield of ∼74%, which was ∼40 times higher than that of the bulk C3 N4 (∼1.76%). ATCN-DSCN enabled a turnover frequency (TOF) of 2.950 h −1, which, to the best of our knowledge, is the highest record of TOF for the photo-regeneration of NADH. For the artificial bio-photoreduction of CO2, sustainable conversion of CO2 to formic acid was achieved with a final formic acid concentration of 290.0 μM after 9 hours of light illumination. The excellent optical and photoelectrical properties of the ATCN-DSCN were enabled by the synergistic effect between the specific porous multishell hollow structure and thiophene ring incorporation, which endowed ATCN-DSCN enhanced light absorption and improved charge separation with boosted photocatalytic regeneration of NADH.